Roadmap to Sustainable Halal Food Business Growth in Developing Countries: Integrating Payment Technology, Digital Marketing and Access to Islamic Financing - Erike Anggraeni; Khavid Normasyhuri; Nurul Aprinita; Tri Atmaja Pramudita Wisnu Kusuma; Adli Rikanda Saputra (Universitas Bangka Belitung, 2025)
The primary issue of this research stems from the phenomenon of disparate technology utilization, restricted digital marketing to specific markets, and challenges in accessing Islamic financing, which collectively hinder the acceleration of the halal food business's growth, despite its substantial market potential in Indonesia. The objective of the study is to enhance the current body of literature regarding the correlation between payment technology, digital marketing, and access to Islamic financing, with a specific emphasis on the expansion of sustainable halal food enterprises in developing nations, particularly Indonesia. Primary data was collected by selecting a sample of respondents, specifically halal food business actors in Indonesia, using a purposive sampling approach. In total, 250 samples were employed in this investigation. The Likert Scale was employed to evaluate the indications, and data were collected using Google Forms. The study's findings indicate that the development of sustainable halal food enterprises in developing countries in Indonesia is influenced by payment technology, digital marketing, and access to Islamic financing. This research contributes to the theoretical literature by enhancing the development of the Technology Acceptance Model (TAM), Digital Marketing Theory, and Islamic Financing Access Theory in the context of the halal food industry in Indonesia. In practice, the findings offer halal food companies practical advice on how to expand their consumer reach through digital marketing, increase transactions through payment technology, and leverage Islamic financing to support business development and improve market competitiveness.